menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Solve for x and y 6(ax + by) = 3a + 2b ; 6(bx-ay) = 3b - 2a
asked
Apr 26, 2022
63.7k
views
0
votes
Solve for x and y
6(ax + by) = 3a + 2b ; 6(bx-ay) = 3b - 2a
Mathematics
high-school
Winterized
asked
by
Winterized
5.3k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
3
votes
6×ax+6×by =6ax+6by =3a+2b,6×bx-6×ay=3b-2a=6bx-3a+2b
Zefiryn
answered
Apr 29, 2022
by
Zefiryn
5.5k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.7m
questions
7.4m
answers
Other Questions
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
Solve for h 3h=7(2/7-3/7h)-10
1/7 + 3/14 equivalent fractions
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org